The Effect of Business Risk, Firm Size and Good Corporate Governance on Company Performance with Capital Structure as an intervening variable (Empirical Study on companies listed in the Business-27 Index on the IDX for the 2016-2020 period) - Oktariani, Siska (International Journal of Economic, Business & Applications, 2022)
This study aims to analyze the effect of business risk, company size, good corporate governance on company performance and analyze the indirect effect of business risk, company size, good corporate governance on company performance with capital structure as an intervening variable. The population of this study includes all companies that are members of the Bisnis-27 index as many as 27 companies. The sampling technique used purposive sampling method with the number of samples that met the criteria as many as 14 companies. Partial Least Square (PLS) is used as a method to analyze the data that has been obtained. The results showed that firm size and good corporate governance had a significant effect on capital structure, while business risk had no effect on capital structure. Business risk, company size, and good corporate governance have no effect on company performance. For indirect testing, it is proven that company size and good corporate governance have an indirect effect on company performance through capital structure as an intervening variable, while business risk has no effect on company performance through capital structure as an intervening variable.